Quantification of Volatile Metabolites Derived From Garlic (Allium sativum) in Human Urine - Scheffler, Laura; Sharapa, Constanze; Buettner, Andrea (Frontiers in Nutrition, 2019)
The consumption of garlic (Allium sativum) is widely known to (negatively) impact body odor, in particular breath and sweat, but also urine. Despite this common phenomenon, the underlying processes in the body that lead to the malodor are not yet fully understood. In previous studies we identified three volatile garlic-derived metabolites in human milk and urine, namely allyl methyl sulfide (AMS), allyl methyl sulfoxide (AMSO) and allyl methyl sulfone (AMSO2). In the present study, we monitored the excretion processes of these metabolites via human urine after consumption of garlic over time, whereby 19 sets of eight urine samples (one sample pre-ingestion and seven samples post-ingestion) were analyzed using two-dimensional high resolution gas chromatography-mass spectrometry/olfactometry (HRGC-GC-MS/O). The highest concentrations of these metabolites were detected in urine ~1-2 h after garlic ingestion, with a second increase observed after 6-8 h in the urine of some participants. Moreover, the highest observed concentrations differed between the individual participants or test series by up to one order of magnitude.